PENGARUH STRUKTUR KEPEMILIKAN, PAJAK, DAN PERTUMBUHAN PERUSAHAAN TERHADAP PEMBAYARAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Muhammad Suyudi; Nyoria Anggraeni Mersa; Astri Rianti Putri (Politeknik Negeri Samarinda, 2020)
The purpose of this study is to examine the effect of ownership structure, tax, and firm growth on dividend payments measured using the Dividend Payout Ratio (DPR). The variable of this study is Ownership Structure as variables X1, Tax as variables X2 and Company Growth as variables X3 and Dividend Payment as variables Y. This study also used multiple linear regression with f test and t test using SPSS 25 program. This study shows that the ownership structure does not have a significant effect on dividend payments and firm growth does not significantly influence dividend payments, but other tax variables significantly influence dividend payments. Keywords: Dividend, Dividend Payout Ratio, ownership structure, tax, growth